Immune-metabolic genesis of pathological processes - Andrei M. Zemskov; Tatiyana A. Berezhnova; Veronika A. Zemskova; Kseniya S. Dyadina; Yana V. Kulintsova; Anton V. Larin (Belgorod National Research University, 2019)
This article deals with metabolic-immune processes at rest and under stress conditions, which, in turn, results in the development of immune-dependent and immune-associated disorders. The article analyzes study results and conclusions of various literature sources and experimental data in healthy individuals and patients suffering from non-specific inflammatory lung diseases; purulent-inflammatory diseases and their combinations, primary and secondary progressive multiple sclerosis in the acute stage and remission. Research studies investigated the impact of the type, stage, combination of diseases on the parameters of the immunologic and metabolic statuses, as well as their correlations. The authors also analyzed metabolic effects of immunomodulators. Based on the analysis of the literature and own clinical and experimental data, the authors identified the ability of metabolic factors to regulate immunological processes. A correlative analysis of examination results of the patients with various diseases helped detect the unity of the immune-metabolic mechanisms of pathology. The data on the therapeutic effect of various modulators through differentiated biochemical chains and vice versa - the metabolic effect through immunological mechanisms -were analyzed in the study. Thus, one can testify that there is the phenomenon of a mediated effect of some immunocorrectors on the reactivity through metabolic chains. The fact that a number of modulators and metabolics can simultaneously affect the biochemical and immunological parameters of patients proved the above phenomenon. There was revealed a significant correlation interaction of the immune-metabolic parameters with various types of purulent-inflammatory diseases, which proves the formation of a single mechanism of pathology.